Thermal power plant : design and operation - Sarkar, Dipak K. (Amsterdam : Elsevier, 2015)
This book discusses various aspects of a thermal power plant, providing a new dimension to the subject, with focus on operating practices and troubleshooting, as well as technology and design. It presents practical content on coal-, gas-, oil-, peat- and biomass-fueled thermal power plants, with chapters on steam power plant systems, start up and shut down, and interlock and protection. It focuses exclusively on thermal power, addressing some new frontiers specific to thermal plants. --
Includes index.
Includes bibliographical references and index.
Online resource; title from PDF title page (ScienceDirect, viewed September 3, 2015).
Elsevier
Keywords: Steam power plants; TECHNOLOGY & ENGINEERING / Mechanical; Steam power plants; Electronic books; Electronic books